Emission analysis of sugarcane bagasse combustion in a burner pilot - Costa, M. A.M. [UNESP]; Schiavon, N. C.B. [UNESP]; Felizardo, M. P.; Souza, A. J.D. [UNESP]; Dussán, K. J. [UNESP] (Elsevier, 2023)
Although biomass is from a renewable source, and its biological development captures CO2, burning emits a mixture of various components, such as particulate materials, CO2, CO, NOx, oxides, VOCs, among others, and may contain F, Hg and As. These gases contribute toward anthropogenic air polluting agents and are emitted for energy sources by various industrial sectors, such as sugarcane bagasse burning, which is a waste product of the sugar and alcohol industry. This study aims to quantify gas emissions, mainly CO2, CO, and NOx, from sugarcane bagasse burning under different burner operating conditions and to evaluate the emission and control of these pollutants using a Venturi scrubber. The sugarcane bagasse combustion process occurred in an experimental burner, comprising a rotary feeder, combustion chamber, exhaust gas chamber, Venturi scrubber, cyclone, blowers, and exhaust ducts. The Venturi scrubber, located between the burner and the cyclone, has a rectangular geometry. The gas velocity was evaluated from 3.4 to 11 m/s and the water flow rates from 2.5 L/min to 6.0 L/min. The results indicate that CO concentrations ranged from 34 to 311 ppm, the NOx concentrations from 8 to 80 ppm, while CO2 reached values from 6000 to 26000 ppm. Investigating and quantifying these emissions are important to understand the global carbon balance, given the considerable magnitude of CO2 emissions from these non-fossil fuels.
Keywords: CO emission; CO2 emission; NOx emission; Pollutant control; Sugarcane bagasse fuel; Venturi scrubber